Spontaneously designed, self-assembled and oriented ZnO nanorods by photoinduced polymerization of epoxydiacrylate formulation in the presence of 2-mercapto-thioxanthone - Kirtay, Hicret; Akbulut, Ozge; Arsu, Nergis (ELSEVIER SCIENCE SA, 2022)
Here we report an environmentally friendly, fast, efficient and low cost method for in-situ preparation of ZnO nanorods in polymer matrix which is obtained using epoxydiacrylate formulation by UV irradiation. Compared to our previous study, the shape of the ZnO nanoparticles even with the same photoinitiator was found to mainly depend on the polymer matrix, but another important finding that was seen from the SEM images is that the type of photoinitiator helped for spontaneous self-assembly and orientation of ZnO nanoparticles. This very important issue arose when the one component Type II photoinitiator, namely, 2-mercapto thioxanthone was used in formulation. Self-assembly and orientation of ZnO nanorods in polymer were not the case either with Thio-xanthone and Thiophenol or in the presence of Type I photoinitiator. All these experimental results for synthesis of ZnO nanoparticles in hydrophilic and hydrophobic polymer matrices may help to understand the effect of photoinitiator and polymer.
Keywords: Polymeric nanocomposites; ZnO nanoparticles; Photoinitiator; 2-Mercapto-thioxanthone; Photopolymerization; PHOTOCHEMICAL-SYNTHESIS; NANOPARTICLES; THIOXANTHONE; GROWTH; NANOSTRUCTURES; NANOCOMPOSITES; CONDUCTIVITY; TEMPERATURE; Chemistry; Materials Science